Dataset of UV induced changes in nuclear proteome obtained by GeLC-Orbitrap/MS in Pinus radiata needles - Sara Alegre; Jesús Pascuala; Matthias Nagler; Wolfram Weckwerth; María Jesús Cañal; Luis Valledor (Elsevier BV, 2025)
Although responses to UV stress have been characterised at system and cellular levels, the dynamics of the nuclear proteome triggered in this situation are still unknown, despite its essential role in regulating gene expression and in last term plant physiology. To fill this gap, we characterised the variations in the nuclear proteome after 2 h and 16 h (8 h/day) of UV irradiation by using state-of-the-art mass spectrometry-based shotgun proteomics methods combined with novel bioinformatics workflows that were employed in the manuscript entitled “The variations in the nuclear proteome reveal new transcription factors and mechanisms involved in UV stress response in Pinus radiata” (Pascual et al., 2016) [1]. We employed in-gel digestion followed by a 120 min gradient prior to MS analysis. Data was processed following two approaches: a database dependent employing the SEQUEST algorithm and custom databases, and a database independent by mass accuracy precursor alignment (MAPA). 388 proteins were identified by SEQUEST search and 9094 m/z were quantified by MAPA. Significant m/z were de novo sequenced using the Novor algorithm. We present here the complete datasets and the analysis workflow.